(untitled) (Research, Society and Development, 2022)
Breastfeeding should be started at birth and continued for at least two years; it should be exclusive and on demand until the sixth month, thereafter supplemented with nutritious foods. Breastfeeding has several advantages for the child, one of which being a lower infant mortality rate. During the COVID-19 pandemic, exposure to food insecurity and indirect effects on the child population are relevant, including health problems related to nutritional status. Objective: To analyze the Diet of Infants at a Teaching Maternity Hospital in Brazil’s Northeast Region during the SARS-CoV-2 Pandemic. Methodology: This epidemiological, observational, retrospective, and analytical investigation was conducted at a breastfeeding clinic in a teaching maternity hospital in Brazil’s Northeast. In the years 2020 and 2021, data were gathered by reviewing paper records of infants released from the aforementioned maternity hospital’s Rooming-in. Results: In this study, 79 infants were evaluated. Within the first hour of life, most infants had skin-to-skin contact (80.33%) and (63.08%) were breastfed. Until the 6th month, 21.52% of babies were exclusively breastfed (EB). Children who had skin-to-skin contact also breastfed within the first hour (p=0.00). Full-term children with adequate weight for age had EBF for at least 1 month of life (p=0.04). Conclusion: The majority of the maternity hospitals investigated continued to practice skin-to-skin contact and breastfeeding in the first hour of infancy despite the COVID-19 epidemic.